Transcendent Selfhood - John B Chethimattam (Journal of Dharma, 2020)
This is a remarkable book, concentrating as it does, on the meaning and function of transcendence in understanding the authentic self of man. The problem we face today is that even a man-oriented civilization like that of the West is too preoccupied with the physical environment to pay any attention to the inner self of man with which religions are concerned. The author finds the basic reason for this loss of self in "the objectivist naturalist attitude" which Husserl in his last years called "the original sin for which the West was being driven into cultural exile." This objectivism which started with the search of the Greeks for the pbysis, the intrinsic nature of things, has led to an absence of transcendence. The Christian faith and mystical subjectivism was not able to prevent the inevitable slide into objectivism and the present crisis. Even Descartes, Kant and the German Romantics who emphasized the subject over against the object, were not able to overcome the objectivist attitude, since "Kant’s subject never exceeded the status of a principle that constitutes objective intelligibility but remains itself unknowable."